Alcoholism is a Disinhibitory Disorder: Neurophysiological Evidence from a Go/No-Go Task - Kamarajan, Chella (2004)
Response inhibition is considered a core dimension in alcoholism and its co-existing disorders. The major objective of this study is to compare the magnitude and spatial distribution of ERP components during response activation and inhibition in alcoholics (N = 30) and normal controls (N = 30) using a visual Go/No-Go task. The results indicate that alcoholics manifest a decreased P3(00) amplitude during Go as well as No-Go conditions. The difference between Go and No-Go processing was more evident in controls than in alcoholics. The topography of current source density in alcoholics during the P3 response was found to be very different from that of normals, suggesting that alcoholics perhaps activated inappropriate brain circuitry during cognitive processing. The significantly reduced No-Go P3 along with the relatively less anteriorized CSD topography during No-Go condition suggests poor inhibitory control in alcoholics. It is proposed that the No-Go P3, the electrophysiological signature of response inhibition, can be considered as an endophenotypic marker in alcoholism.